2008
DOI: 10.1016/j.jneuroim.2008.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of experimental autoimmune encephalomyelitis by a novel small molecular weight proinflammatory cytokine suppressing drug

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a T cell-mediated, autoimmune disease of the central nervous system (CNS) that serves as a model for various cellular and molecular aspects of the human disease, multiple sclerosis (MS). Although EAE has long been considered a T cellmediated disease, macrophages play a role in disease pathogenesis and are known to accumulate in the CNS under the control of chemokines. In the present report we demonstrate that mice induced to develop EAE were treated with a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…The linkage between changes in proinflammatory cytokine levels and neurologic outcomes, revealed by the improvement in synaptic endpoints (synaptic protein levels and LTP) after attenuation of proinflammatory cytokine levels by MW-151 treatment, is consistent with previous reports of MW-151 efficacy in other rodent CNS injury models, including oligomeric Aβ-induced injury (Hu et al, 2007), kainic acid-induced seizures (Somera-Molina et al, 2007, 2009), TBI models (Lloyd et al, 2008; Chrzaszcz et al, 2010), and the EAE model of multiple sclerosis (Karpus et al, 2008). These previous studies documented that MW-151 efficacy at reducing injury-induced upregulation of proinflammatory cytokine levels was associated with a reduction in long-term neuronal injury and attenuation of hippocampal-dependent cognitive deficits.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The linkage between changes in proinflammatory cytokine levels and neurologic outcomes, revealed by the improvement in synaptic endpoints (synaptic protein levels and LTP) after attenuation of proinflammatory cytokine levels by MW-151 treatment, is consistent with previous reports of MW-151 efficacy in other rodent CNS injury models, including oligomeric Aβ-induced injury (Hu et al, 2007), kainic acid-induced seizures (Somera-Molina et al, 2007, 2009), TBI models (Lloyd et al, 2008; Chrzaszcz et al, 2010), and the EAE model of multiple sclerosis (Karpus et al, 2008). These previous studies documented that MW-151 efficacy at reducing injury-induced upregulation of proinflammatory cytokine levels was associated with a reduction in long-term neuronal injury and attenuation of hippocampal-dependent cognitive deficits.…”
Section: Discussionsupporting
confidence: 91%
“…The active pharmaceutical used for biological studies was the dihydrochloride hydrate for of the water-soluble, acidic drug. Low doses per administration were employed as noted, and are similar to those used previously for efficacy in diverse animal models of CNS diseases that involve excessive proinflammatory cytokine production as part of the pathology progression mechanism, including a model of early AD (Hu et al, 2007), TBI (Lloyd et al, 2008; Chrzaszcz et al, 2010), multiple sclerosis (Karpus et al, 2008), and seizures (Somera-Molina et al, 2007, 2009) at low doses similar to that used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The improved outcomes with Mzc administration in multiple acute or chronic injury models where proinflammatory cytokine upregulation contributes to neurologic injury (Hu et al, 2007; Somera-Molina et al, 2007; Karpus et al, 2008; Lloyd et al, 2008) suggest that disease-specific interventions may be more effective if combined with therapies that modulate glial responses. These results are additional evidence that glial activation may be a common pathophysiologic mechanism and therapeutic target in diverse forms of neurologic injury (Akiyama et al, 2000; Craft et al, 2005; Emsley et al, 2005; Hu et al, 2005; Perry et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We developed [ 9 ] a CNS-penetrant, small molecule experimental therapeutic, MW01-2-151WH (MW151), that selectively restores injury- or disease-induced overproduction of proinflammatory cytokines towards homeostasis. MW151 is efficacious in a variety of animal models of diseases where proinflammatory cytokine overproduction is a component of disease progression, including (1) animal models of Alzheimer’s disease [ 9 , 10 ]; (2) neurologic sequelae of seizures [ 11 , 12 ]; (3) EAE model of multiple sclerosis [ 13 ]; (4) a ‘two-hit’ injury model of increased susceptibility to seizures after a TBI [ 14 ], and (5) radiation-induced cognitive impairment [ 15 ]. Particularly relevant to the current study, we have previously reported [ 16 ] that MW151 is efficacious in a closed head injury (CHI) model of diffuse TBI in mice, when administered during the time of the acute post-injury cytokine surge.…”
Section: Introductionmentioning
confidence: 99%